2006
DOI: 10.1103/physrevb.74.024107
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopy and x-ray diffraction ofCd(OH)2to28G

Abstract: We report Raman and infrared absorption spectroscopy along with X-ray diffraction for brucitetype β-Cd(OH) 2 to 28 GPa at 300 K. The OH-stretching modes soften with pressure and disappear at 21 GPa with their widths increasing rapidly above 5 GPa, consistent with a gradual disordering of the H sublattice at 5-20 GPa similar to that previously observed for Co(OH) 2 . Asymmetry in the peak shapes of the OH-stretching modes suggests the existence of diverse disordered sites for H atoms in Cd(OH) 2 under pressure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
3
9
0
1
Order By: Relevance
“…While Kruger et al (1989) also observed a pressure dependence of −0.6 cm −1 /GPa for the IR-active OH stretching mode, by high-pressure FTIR experiment on Mg (OH) 2 up to 30 GPa. Similar negative pressure dependence for the internal OH stretching modes have also been observed in other brucite-type minerals, such as Ca (OH) 2 (Kruger et al, 1989), β-Ni (OH) 2 (Murli et al, 2001), Co (OD) 2 (Shieh & Duffy, 2002), Fe (OH) 2 (Speziale et al, 2005), and Cd (OH) 2 (Shim et al, 2006).…”
Section: 1029/2019jb017934supporting
confidence: 79%
“…While Kruger et al (1989) also observed a pressure dependence of −0.6 cm −1 /GPa for the IR-active OH stretching mode, by high-pressure FTIR experiment on Mg (OH) 2 up to 30 GPa. Similar negative pressure dependence for the internal OH stretching modes have also been observed in other brucite-type minerals, such as Ca (OH) 2 (Kruger et al, 1989), β-Ni (OH) 2 (Murli et al, 2001), Co (OD) 2 (Shieh & Duffy, 2002), Fe (OH) 2 (Speziale et al, 2005), and Cd (OH) 2 (Shim et al, 2006).…”
Section: 1029/2019jb017934supporting
confidence: 79%
“…Its low intensity and large width are consistent with expectations for the vibration mode (E g (R)) and tentatively has assigned to the vibrational mode of Cd (OH) 2 . [23] Our Raman analysis provides significance of the growth temperature for size manipulation and subsequent effect on the Raman spectra of CdO nano product.…”
Section: Resultsmentioning
confidence: 99%
“…Four corners of each octahedron are occupied by water molecules, and the remaining two apices by the oxygen atoms belonging to sulfate groups. 20 This may lead to the formation of SO 4 tetrahedra with relatively longer and shorter S-O bond lengths in the structure coordinated with CdO 6 octahedra. The guanidinium groups are located above and below these layers.…”
Section: Site Symmetry Free -Ion Symmetrymentioning
confidence: 99%
“…Hydrogen bonds from the water molecules connect these clusters to form layers. 20,21 The sulfate group with its T d symmetry usually has S-O bond lengths around 1.47Å and O-S-O angles around 109°in its free state. One corner of each tetrahedron points away from the layer, since no hydrogen bonding from this oxygen atom to the O-H groups within the layer is possible.…”
Section: Site Symmetry Free -Ion Symmetrymentioning
confidence: 99%